2018
DOI: 10.13080/z-a.2018.105.008
|View full text |Cite
|
Sign up to set email alerts
|

Screening of early maturing soybean genotypes for production of high quality edible oil

Abstract: The usage and value of soybean (Glycine max (L.) Merr.) seed oil are mainly determined by its fatty acid composition, which affects physical, chemical and nutritional properties. In order to assess genotypes' suitability for edible oil production and determine the variability in phenotypic expression of the amount of oil and fatty acid composition in the seed, three-year (2010-2012) trials were set up with eight early maturing advanced soybean lines. As a result, we determined the amount of seed oil and compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…Kočar et al [127] was 7.36, which falls within the recommended range for vegetable oils suggested by Rani et al [126], meaning that tested genotypes can produce nutritionally acceptable oil. On the other hand, very high LA/ALA is considered detrimental for human health, and so lowering it by breeding can help with the prevention against degenerative pathologies [130].…”
Section: Oil Content and Fatty Acid Compositionsupporting
confidence: 70%
See 4 more Smart Citations
“…Kočar et al [127] was 7.36, which falls within the recommended range for vegetable oils suggested by Rani et al [126], meaning that tested genotypes can produce nutritionally acceptable oil. On the other hand, very high LA/ALA is considered detrimental for human health, and so lowering it by breeding can help with the prevention against degenerative pathologies [130].…”
Section: Oil Content and Fatty Acid Compositionsupporting
confidence: 70%
“…According to Josipović et al [66] and Popović et al [71], the amount of oil in soybean seed was significantly higher in years with less precipitation and higher air temperatures at the time of pod formation and dry matter accumulation. This was also true for the average oil content determined by Matoša Kočar et al [127], noting that hot and extremely humid conditions resulted in the lowest average amount of oil in soybean seed, whereas hot and dry conditions resulted in higher average amounts of oil. On the other hand, Vollmann et al [61] reported that low precipitation rates and high temperatures did not favour oil synthesis and that, in genotypes of later maturity, oil synthesis was enhanced by late water availability.…”
Section: Oil Content and Fatty Acid Compositionsupporting
confidence: 59%
See 3 more Smart Citations